The fracture energy of ruptures driven by flash heating - Nicolas Brantut; Robert C. Viesca (Geophysical Research Letters)
Abstract We present a model for dynamic weakening of faults based on local flash heating at microscopic asperity contacts coupled to bulk heating at macroscopic scale. We estimate the fracture energy G associated with that rheology and find that for constant slip rate histories G scales with slip δ as G∝δ2 at small slip, while G∝δ1/2 at large slip. This prediction is quantitatively consistent with data from laboratory experiments conducted on dry rocks at constant slip rate. We also estimate G for crack‐like ruptures propagating at constant speed and find that G∝δ2/3 in the large slip limit. Quantitative estimates of G in that regime tend to be several orders of magnitude lower than seismologically inferred values of G. We conclude that while flash heating provides a consistent explanation for the observed dynamic weakening in laboratory experiments with kinematically imposed slip, its contribution to the energy dissipation during earthquakes becomes negligible for large events when considering the elastodynamic coupling between strength and slip evolution.